Napoleon: Eine Novelle - Sternheim, Carl, 1878-1942 (Salt Lake City, UT : Project Gutenberg, 2012)
"Napoleon: Eine Novelle" by Carl Sternheim is a novella written during the early 20th century. This work explores the life and ambitions of a character named Napoleon, who is not the famed French general but instead a cook and owner of a restaurant in Paris. The novella delves into themes of identity, ambition, and the gastronomic culture of the time, illustrating the protagonist's journey through the culinary and social landscapes of society. The story follows Napoleon from his childhood in Waterloo to his rise as the celebrated owner of a restaurant called "Chapon fin" in Paris. As he navigates through various relationships, including a romance with the dancer Valentine, he becomes increasingly disillusioned with the superficial nature of wealth and social status. Ultimately, after achieving fame and success in the competitive restaurant world, he faces devastating loss when Valentine is executed during the violence of the Paris Commune. This tragedy propels him into a deep introspection about life, death, and the human condition, leading him to a state of mourning and reflection on his past. In the end, he finds solace in nature and the simplicity of life, indicating a profound transformation rooted in suffering and the passage of time. (This is an automatically generated summary.)
Release date is 2012-11-17
Produced by Jens Sadowski
Keywords: Napoleon I, Emperor of the French, 1769-1821 -- Fiction